/
/
/
Let f(x) = 8x^2 - 5x and g(x) = 7x + 9. Find the composite.
Not my Question
Flag Content

# Question : Let f(x) = 8x^2 - 5x and g(x) = 7x + 9. Find the composite. : 2151610

MULTIPLE CHOICE. Choose the one alternative that best completes the statement or answers the question.

Let f(x) = 8x2 - 5x and g(x) = 7x + 9.

Find the composite.

1) f[g(3)]

A) 618

B) 408

C) 7050

D) 1212

2) g[f(3)]

A) 618

B) 408

C) 7050

D) 1212

3) f[g(-3)]

A) 618

B) 1212

C) 7050

D) 408

4) g[f(-3)]

A) 408

B) 618

C) 7050

D) 1212

5) f[g(k)]

A) 392k2 + 973k + 603

B) 56k2 + 35k + 9

C) 56k2 - 35k + 9

D) 392k2 - 973k + 603

6) g[f(k)]

A) 56k2 + 35k + 9

B) 392k2 + 973k + 603

C) 56k2 - 35k + 9

D) 392k2 - 973k + 603

7) f[g(-k)]

A) 392k2 + 973k + 603

B) 56k2 - 35k + 9

C) 56k2 + 35k + 9

D) 392k2 - 973k + 603

8) g[f(-k)]

A) 56k2 + 35k + 9

B) 392k2 + 973k + 603

C) 392k2 - 973k + 603

D) 56k2 - 35k + 9

9) f[g(-4)]

A) 37

B) 148

C) 2983

D) 765

10) g[f(4)]

A) 37

B) 148

C) 765

D) 2983

Find f[g(x)] and g[f(x)].

11) f(x) = 5x + 9; g(x) = 4x - 7

A) f[g(x)] = 20x + 26

g[f(x)] = 20x - 29

B) f[g(x)] = 20x - 26

g[f(x)] = 20x + 29

C) f[g(x)] = 20x - 29

g[f(x)] = 20x + 26

D) f[g(x)] = 20x + 29

g[f(x)] = 20x - 26

12) f(x) = 5x3 + 8; g(x) = 2x

A) f[g(x)] = 40x3 + 16

g[f(x)] = 10x3 + 8

B) f[g(x)] = 40x3 + 8

g[f(x)] = 10x3 + 16

C) f[g(x)] = 10x3 + 8

g[f(x)] = 40x3 + 16

D) f[g(x)] = 10x3 + 16

g[f(x)] = 40x3 + 8

13) f(x) = (2/x); g(x) = 2x3

A) f[g(x)] = 1/x3; g[f(x)] = 4/x3

B) f[g(x)] = 4/x3; g[f(x)] = 1/x3

C) f[g(x)] = 1/x3; g[f(x)] = 16/x3

D) f[g(x)] = 16/x3; g[f(x)] = 1/x3

14) f(x) = 7/(x)4; g(x) = 2x3

A) f[g(x)] = 7x12/686

g[f(x)] = x12/16

B) f[g(x)] = 7/16x12

g[f(x)] = 686/(x)12

C) f[g(x)] = 686/7x12

g[f(x)] = 16/(x)12

D) f[g(x)] = 7x12/16

g[f(x)] = x12/686

15) f(x) = √(x + 5); g(x) = 4x - 1

A) f[g(x)] = √(4x2 + 1)

g[f(x)] = √(4x2 - 5)

B) f[g(x)] = √(4x2 - 5)

g[f(x)] = √(4x2 - 5)

C) f[g(x)] = 2√(x + 5)

g[f(x)] = 4√(x + 1) - 1

D) f[g(x)] = 2√(x + 1)

g[f(x)] = 4√(x + 5) - 1

16) f(x) = (1/x - 5); g(x) = x + 5

A) f[g(x)] = 1/(x + 5)

g[f(x)] = x - 5

B) f[g(x)] = x - 5

g[f(x)] = 1/(x + 5)

C) f[g(x)] = (5x - 24)/(x - 5)

g[f(x)] = 1/x

D) f[g(x)] = 1/x

g[f(x)] = (5x - 24)/(x - 5)

17) f(x) = 5x2; g(x) = x + 3

A) f[g(x)] = 5x2 + 30x + 45

g[f(x)] = 5x2 + 3

B) f[g(x)] = 5x2 + 30x + 3

g[f(x)] = 5x2 + 45

C) f[g(x)] = 5x2 + 3

g[f(x)] = 5x2 + 30x + 49

D) f[g(x)] = 5x2 + 45

g[f(x)] = 5x2 + 30x + 3

18) f(x) = x2 + 2x + 3; g(x) = x - 4

A) f[g(x)] = x2 + 2x - 1

g[f(x)] = x2 - 6x + 11

B) f[g(x)] = x2 + 2x - 1

g[f(x)] = x2 + 6x + 11

C) f[g(x)] = x2 - 6x + 11

g[f(x)] = x2 + 2x - 1

D) f[g(x)] = x2 + 6x + 11

g[f(x)] = x2 + 2x - 1

19) f(x) = √(x - 6); g(x) = 6x2 + 7

A) f[g(x)] = √(6x2 - 6)

g[f(x)] = 6(x - 6)2 + 7

B) f[g(x)] = √(6x2 + 7) - 6

g[f(x)] = 6x + 1

C) f[g(x)] = √(6x2 + 1)

g[f(x)] = 6x - 29

D) f[g(x)] = 6x - 29

g[f(x)] = √(6x2 + 1)

20) f(x) = (7/x); g(x) = √(x - 6)

A) f[g(x)] = (7/√(x) - 6)

g[f(x)] = √((7 - 6x/x))

B) f[g(x)] = (7/√(x) - 6)

g[f(x)] = √((7/x)) - 6

C) f[g(x)] = (7/√(x - 6))

g[f(x)] = √((7 - 6x/x))

D) f[g(x)] = (7/√(x - 6))

g[f(x)] = √((7/x)) - 6

Write the function as the composition of two functions f and g such that y = f[g(x)]).

21) y = (1/x2 - 7)

A) f(x) = (1/x2), g(x) = - (1/7)

B) f(x) = (1/x), g(x) = x2 - 7

C) f(x) = (1/7), g(x) = x2 - 7

D) f(x) = (1/x2), g(x) = x - 7

22) y = (5/x2) + 8

A) f(x) = (1/x), g(x) = (5/x) + 8

B) f(x) = x, g(x) = (5/x) + 8

C) f(x) = (5/x2), g(x) = 8

D) f(x) = x + 8, g(x) = (5/x2)

23) y = (5/√(8x + 5))

A) f(x) = (5/√(x)), g(x) = 8x + 5

B) f(x) = 5, g(x) = √(8 + 5)

C) f(x) = (5/x), g(x) = 8x + 5

D) f(x) = √(8x + 5), g(x) = 5

24) y = (3x - 18)7

A) f(x) = 3x7, g(x) = x - 18

B) f(x) = (3x)7, g(x) = -18

C) f(x) = 3x - 18, g(x) = x7

D) f(x) = x7, g(x) = 3x - 18

25) y = √(6 + 6x2)

A) f(x) = 6 + 6x2, g(x) = √(x)

B) f(x) = √(x), g(x) = 6 + 6x2

C) f(x) = √(6 + 6x), g(x) = x

D) f(x) = (4)√(6 + 6x2), g(x) = (4)√(6 + 6x2)

26) y = (x1/2 + 9)3 + 4(x1/2 + 9)2 - 6

A) f(x) = (x + 9)3 + 4(x + 9)2 - 6, g(x) = x1/2 + 9

B) f(x) = x3 + 4x2 - 6, g(x) = x1/2 + 9

C) f(x) = (x + 9)3 + 4x2 - 6, g(x) = x1/2

D) f(x) = x1/2 + 9, g(x) = x3 + 4x2 - 6

## Solution 5 (1 Ratings )

Solved
Calculus 3 Months Ago 23 Views